2012
DOI: 10.2308/ajpt-10259
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Initial Information Ambiguity on the Accuracy of Analytical Review Judgments

Abstract: SUMMARY Analytical procedures require that auditors develop and test hypotheses about possible fluctuations in a firm's financial data. Research in psychology suggests that the initial information ambiguity that exists prior to hypothesis generation may affect not only the initial hypothesis set, but also final judgment accuracy. We argue in this paper that information ambiguity can be caused by two primary variables, data sufficiency and data complexity, and examine how these variables affect j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 30 publications
0
13
0
5
Order By: Relevance
“…They then are provided with a second nonvarying set of information and are asked to determine the error in the data. Luippold and Kida's () results indicate that when auditors are initially exposed to more ambiguous information, they do not perform as well at identifying the errors in the financial statements in both their hypotheses and final conclusions, as compared to those that are initially exposed to unambiguous data.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…They then are provided with a second nonvarying set of information and are asked to determine the error in the data. Luippold and Kida's () results indicate that when auditors are initially exposed to more ambiguous information, they do not perform as well at identifying the errors in the financial statements in both their hypotheses and final conclusions, as compared to those that are initially exposed to unambiguous data.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
“…In a similar vein, Luippold and Kida () investigate the impact of ambiguity in the initial data provided to auditors on performance of two key components of analytical procedures (hypothesis testing and decision accuracy). They vary the level of ambiguity via data sufficiency and data complexity provided to the auditors.…”
Section: Literature Review By Audit Taskmentioning
confidence: 99%
“…These studies have generated a wide variety of findings regarding how auditors investigate, analyze, and reach conclusions during analytical procedures. For instance, this research has found that the following all impact auditors' ability to identify the correct cause of a fluctuation: (Bhattacharjee et al 1999;Luippold and Kida 2012), accountability (Peecher 1996;Asare et al 2000), decision aids (Anderson and Koonce 1998;Mueller and Anderson 2002;Anderson et al 2003), problem representations/mental models (Bierstaker et al 1999;O'Donnell and Perkins 2011;Brewster 2012), time constraints (Bhattacharjee et al 1999;Asare et al 2000), type of financial statement error (Green and Trotman 2003;Law and Willett 2004), and inconsistent information (Asare and Wright 2003).…”
Section: Prior Analytical Procedures Researchmentioning
confidence: 99%
“…It refers to papers that approach subjective factors, which may in uence the auditor's judgment in the process of the auditing service. As examples we may point out the existence or lack of materiality, auditors' mood, evaluate competence of subordinates/audit pairs, and tasks implementation (Cianci & Bierstaker, 2009;Luippold & Kida, 2012;Pike, Curtis, & Chui, 2013). It decreased in emphasis almost by half (6.8%), despite its presence during all the research period, and was found in 13-21 publications.…”
Section: Declining Themesmentioning
confidence: 99%